PENGARUH DIKLAT DAN CAREER DEVELOPMENT TERHADAP KINERJA KARYAWAN DI PT ANGKASA PURA I CABANG BANDARA INTERNASIONAL I GUSTI NGURAH RAI - BALI: introduction, methods, results and discussion, conclusions, and bibliography. - Adisanti Bhaskara; Cokorda Gede Putra Yudistira; Ni Kadek Dessy Hariyanti (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2023)
Training is an important factor determining the long-term success and profitability of a company. Conversely, employees who maximize their performance also pay attention to their position and achievements in the company, whether they are able to improve so that they get a bigger feeling, or just stay put. Training activities at PT Angkasa Pura I Branch of I Gusti Ngurah Rai International Airport - Bali experienced ups and downs due to the impact of the Covid-19 pandemic which caused system and order changes. This affects the fluctuating performance of employees. On the other hand, the element of subjectivity in career development also affects the performance of the employees themselves. This study examines the effect of Education and Training and Career Development on the performance of employees of PT Angkasa Pura I Branch of I Gusti Ngurah Rai International Airport - Bali. The research sample is 109 company employees. Questionnaires were distributed online using the proportional stratified random sampling method. Data were processed with SPSS, multiple linear regression analysis method. The results showed that education and training had a significant positive effect on employee performance, career development had a significant positive effect on employee performance, and training and career development had a positive effect simultaneously on employee performance. The output of this thesis is in the form of Evaluation Training which is expected to be able to improve the actual problems faced by the company. This program is summarized and packaged in a book which is used as a reference in carrying out Evaluation Training activities. keywords: Training, Career Development, Employee’s Perfomance, Evaluation Training